The microbiome and its publics: A participatory approach for engaging publics with the microbiome and its implications for health and hygiene - Hodgetts, T; Grenyer, R; Greenhough, B; McLeod, C; Dwyer, A; Lorimer, J (EMBO Press, 2018)
The last twenty years have seen significant falls in the cost and time required for DNA sequencing. The rise of high-throughput (or next generation) sequencing has helped map the microbiome, identifying large numbers of microbial taxa in samples gathered directly from the environment. Much ongoing research is engaged with basic natural history, describing what life is there, and how it functions and interacts. Microbiome science has developed most rapidly in the context of the human body. Although there is still a great deal of uncertainty about what is a normal or healthy human microbiome, microbial ‘dysbiosis’ has been implicated in a range of non-communicative diseases.